Pengaruh Pembelajaran Tari Kreasi Melalui PJBL terhadap Berpikir Kreatif Siswa di SMKN 15 Bandung - Riri Triyani; Lilis Sumiati; Nurwani (Universitas Negeri Medan, 2026)
This study aims to analyze the effect of creative dance learning through Project Based Learning (PjBL) on the creative thinking skills of vocational high school students. This research was motivated by the demands of the Merdeka Curriculum and the Pancasila Student Profile, which emphasize creativity as an important competency. The method used was an experiment with a quantitative approach involving 35 tenth-grade students at SMKN 15 Bandung. Data collection techniques included observation, interviews, and documentation. The results of the study show a significant increase in students' creative thinking skills after the implementation of PjBL in creative dance learning. This is evidenced by a significant difference between the pretest and posttest scores with a t-test result showing a p-value of 0.000 < 0.05. Thus, it can be concluded that PjBL learning is effective in improving students' creative thinking skills.